2010
DOI: 10.1086/649579
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony and Stability of Food Webs in Metacommunities

Abstract: Synchrony has fundamental but conflicting implications for the persistence and stability of food webs at local and regional scales. In a constant environment, compensatory dynamics between species can maintain food web stability, but factors that synchronize population fluctuations within and between communities are expected to be destabilizing. We studied the dynamics of a food web in a metacommunity to determine how environmental variability and dispersal affect stability by altering compensatory dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(148 citation statements)
references
References 49 publications
5
142
1
Order By: Relevance
“…B 281: 20140633 characteristics of nearby lakes, and differences in the seasonal forcing regime of spatially distant lakes, may ensure that compensatory dynamics lack coherence across study sites and/or regions. In addition, metacommunity models have shown that locally driven compensatory dynamics can be quickly overcome by environmental-and dispersal-driven synchronization [40] suggesting that compensatory dynamics may be unstable in the presence of other regional factors. In addition to these broader patterns, our method also revealed scale-specific temporal changes in synchrony and compensation.…”
Section: Discussionmentioning
confidence: 99%
“…B 281: 20140633 characteristics of nearby lakes, and differences in the seasonal forcing regime of spatially distant lakes, may ensure that compensatory dynamics lack coherence across study sites and/or regions. In addition, metacommunity models have shown that locally driven compensatory dynamics can be quickly overcome by environmental-and dispersal-driven synchronization [40] suggesting that compensatory dynamics may be unstable in the presence of other regional factors. In addition to these broader patterns, our method also revealed scale-specific temporal changes in synchrony and compensation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, migration was unidirectional, corresponding to external or forced synchronization simulating , for example, unidirectional dispersal due to predominating winds or water flow. Almost all the theory on synchronized community and population dynamics in chaotic systems is developed for bidirectional dispersal or as reaction-diffusion model allowing for mutual synchronization 7,44,45 . One condition for phase locking of forced chaotic systems (that is, unidirectional dispersal) is that the mismatch between the instantaneous phase of the driver and response population is relatively small 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The degree of asynchrony can explain variation in the connectivity-stability relationship among types of food web networks (Amarasekare 2008) and environmental perturbations (Gouhier et al 2010). In a simple two-patch predator-prey system, Jansen (1995) found that asynchrony in populations allowed a two-patch system to persist longer than a single-patch system.…”
Section: Asynchrony-type Mechanismsmentioning
confidence: 99%